Pengaruh Hedonic Value Dan Utilitarian Value Terhadap Minat Beli Konsumen Uniqlo dengan sikap Konsumen sebagai Mediasi - Michael Michael; Aditya Burhan (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This study aims to analyze the influence of hedonic value and utilitarian value on purchase intention toward Uniqlo products in Indonesia, with consumer attitude as a mediating variable. Utilizing a causal quantitative approach, data were collected via questionnaires from 161 Uniqlo consumers through both offline and online channels. The data analysis methods include instrument validity and reliability tests, normality tests, multiple linear regression analysis, and the Sobel Test to evaluate the mediation effect. The results indicate that hedonic value, utilitarian value, and consumer attitude have a positive and significant influence on purchase intention. Consumer attitude was found to be the most dominant factor influencing purchase intention, with a regression coefficient value of 0.451. Simultaneously, this research model is able to explain 57.3% of the variation in consumer purchase intention. Furthermore, the Sobel Test results confirm that consumer attitude significantly functions as a partial mediator that optimizes the influence of hedonic value (Z = 2.357) and utilitarian value (Z = 3.518) on purchase intention. Practically, Uniqlo focus on building positive consumer attitudes to enhance purchase intention.